2021
DOI: 10.1101/2021.07.07.451468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NGF-p75 signaling coordinates skeletal cell migration during bone repair

Abstract: Tissue repair relies on the coordination of mesenchymal precursor cells (MPCs) which migrate into the injury site, along with the invasion of blood vessels and sensory nerves. Our prior observations found that the neurotrophin Nerve growth factor (NGF) regulates sensory nerve ingrowth to skeletal repair sites via its high-affinity receptor. A body of work in cancer biology suggest that neurotrophins also engage their low-affinity receptor p75 to mediate cellular migration. Here, we observed conditional deletio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…While loss-of-function studies are complicated by the essential and systemic role of neuronal signaling, the laterality of the bone-healing response with concomitant brain injury suggests there is underlying neuronal influence to endochondral repair (Morioka et al 2019). Furthermore, mice lacking Ngf in myeloid cells demonstrate reduced migration of osteogenic precursors, which, together with the differential immune response found in the previous study, suggests a high level of connection between the neural and inflammatory responses (Morioka et al 2019; Xu, Li, et al 2022). Gain-of-function studies show that treatment of bone during development and repair with NGF promotes endochondral ossification and osteogenic progression (Tomlinson et al 2017; Rivera et al 2020).…”
Section: Clinical Implications Of Mechanisms Of Bone Regenerationsupporting
confidence: 61%
See 1 more Smart Citation
“…While loss-of-function studies are complicated by the essential and systemic role of neuronal signaling, the laterality of the bone-healing response with concomitant brain injury suggests there is underlying neuronal influence to endochondral repair (Morioka et al 2019). Furthermore, mice lacking Ngf in myeloid cells demonstrate reduced migration of osteogenic precursors, which, together with the differential immune response found in the previous study, suggests a high level of connection between the neural and inflammatory responses (Morioka et al 2019; Xu, Li, et al 2022). Gain-of-function studies show that treatment of bone during development and repair with NGF promotes endochondral ossification and osteogenic progression (Tomlinson et al 2017; Rivera et al 2020).…”
Section: Clinical Implications Of Mechanisms Of Bone Regenerationsupporting
confidence: 61%
“…Gain-of-function studies show that treatment of bone during development and repair with NGF promotes endochondral ossification and osteogenic progression (Tomlinson et al 2017; Rivera et al 2020). NGF is expressed after axial and cranial bone injury along with the high-affinity TrkA and low-affinity p75 receptors in a variety of cells, including chondrocytes, osteoblasts, and mesenchymal cells (Rivera et al 2020; Xu, Li, et al 2022). NGF has also been shown to be involved in intramembranous repair of long bone stress fractures and cranial bones (Li et al 2019; Xu, Li, et al 2022).…”
Section: Clinical Implications Of Mechanisms Of Bone Regenerationmentioning
confidence: 99%
“…In contrast, sympathetic nerve fibers, which inhibit the increase in bone mass, were not significantly affected. In combination with our transcriptome sequencing data ( Xu et al, 2022 ), we found high expression of Sema3A locally in bone injury sites. Based on its role in bone remodeling, we hypothesize that Sema3A also plays an important regulatory role in bone repair by stimulating sensory nerve innervation and thus promoting bone regeneration.…”
Section: Introductionsupporting
confidence: 64%
“…Interestingly, we found that NGF also regulated the migration of MSCs. Locally released NGF recruited the aggregation of MSCs to the defect site via the NGF-p75 signaling pathway, thereby coupling the neuro-skeletal interaction ( Figure 2 ) ( Xu et al, 2022 ). Despite these findings, we have yet to address the downstream molecular mechanisms of neuroskeletal intercommunication.…”
Section: Introductionmentioning
confidence: 99%
“…Among the top 3 upregulated genes in Zfp467-/-COBs, Wdfy1 plays an important role in the innate immune responses by mediating TLR3/4 signaling (25,26), which might be also involved in the regulation of osteoblast metabolism and function (27,28). Another significantly upregulated gene, Ngfr in Zfp 467-/-cells was found to be required for skeletal cell migration and osteogenesis, especially during injury repair (29,30). NGFR could also mediate AMP-induced modulation of ERK1/2 and AKT cascades (31), which is consistent with our GSEA pathways enrichment.…”
Section: Discussionmentioning
confidence: 99%